ANALISIS ASUPAN LEMAK, NATRIUM DAN SERAT BERDASARKAN TEKANAN DARAH PADA MAHASISWA PROGRAM STUDI ILMU GIZI FAKULTAS ILMU-ILMU KESEHATAN UNIVERSITAS ESA UNGGUL TAHUN 2016 - Wahyuni, Yulia (Lembaga Penerbitan Unversitas Esa Unggul, 2016)
AbstractBackground: The pressure of blood is a power for the flowingof the blood (oxygen and food) in the arteries, arterioles, pillaries and venous system, thus forming a blood flow to the settle. An increase or decrease in blood pressure will affect the homeostasis of the body. The Food intake is one of the etiology of an increase or decrease in the blood pressure. Some nutrients can increase or decrease the blood pressure is in the intake of fat, and fiber natium.Subject: This research try to explore the relationship between the intake of fat, sodium and fiber on blood pressure. Method:This research conducted on students of department of nutritional sciences in Esa Unggul Universityfor The Academic Year in 2015/2016 were selected by cluster random sampling. The data was taken which the blood pressure, intake of fat, sodium and fiber. The measure of blood pressure issfigmomanometer, the intake fat, fiber, sodium recorded withfood recall 24 hours dan food frequency questionnaire (FFQ).The Result:Subjects in this study are dominated withstudent about 115 peoples with an average age of20 ± 1.6, while the students of7 people (5.74%) with a mean age of20 ± 1.7 years. Daily sodium intake in the group of men more than AKN of 2012 by 14.56% whereas in the group of women less than AKN 2012 amounted to 6.77%. Daily fiber intake in the group of men and women is lower than AKS 2012. Lack of fiber intake on women's groups to 1.42% while the male group 13.19%. Results indicating that there are differences in the intake of fat, sodium and fiber in the group of normal blood pressure, prehypertension and hypertension group with F count 6.574 and P: 0.049 (< 0.05), F count fiber intake 5.431 and P 0.001 (<0, 05) F count 4.765 with P = 0.036 (< 0.05). Spearman rank analysis results indicate that there is a relationship between the intake of fat, fiber and sodium on blood pressure at p < 0.05.Keywords: Student, fat, fiber AbstrakLatar belakang: Tekanan darahsebagai daya untukmengalirnya darah (oksigen dan makanan) di dalam arteri, arteriola, kapiler dan sistem vena, sehingga terbentuklah suatu aliran darah yang menetap. Peningkatan atau penurunan tekanan darah akan mempengaruhi homeostasis tubuh.Asupan makan merupakan salah satu etiologi peningkatan atau penurunan tekanan darah.Beberapa zat gizi yang dapat meningkatkan/menurunkan tekanan darah adalah asupan lemak, natium dan serat. Tujuan: Mengetahui hubungan asupan lemak, natrium dan serat terhadap tekanan darah baik sistol maupun diastole.Metode: Penelitian ini dilakukan pada mahasiswa prodi ilmu gizi universitas esa unggul tahun akademik 2015/2016 yang dipilih secara cluster random sampling. Hasil: Subjek dalam penelitian ini didomisasi mahasiswi sebanyak 115 orang (94,26 %) dengan rerata usia 20 ± 1,6sedangkan mahasiswasebanyak 7 orang (5,6%) dengan rerata usia 20 ± 1,7 tahun. Hasil uji one way anova menunjukkan bahwa adaperbedaan asupan lemak, natrium dan serat pada kelompok tekanan darah normal, prehipertensi dan kelompok hipertensi dengan nilai F hitung 6,574 dan P : 0,049 (<0,05), Nilai F hitung asupan serat 5,431 dan P 0,001(<0,05)F hitung 4,765 dengan P=0,036 (<0,05). Hasil analisis rank sperman menunjukkan bahwa ada hubungan antara asupan lemak, natrium dan serat dengan nilai p :0,03, 0,25 dan 0,01(p<0,05) dengan nilai r 0,56, 0,84 dan 0,89. Kata kunci: Mahasiswa, lemak, serat